Ø±Ø«Ø§Ø¡ Ø§Ù„Ø®Ù†Ø³Ø§Ø¡ Ù„Ø£Ø®ÙˆÙŠÙ‡Ø§ ÙÙŠ Ø´Ø¹Ø±Ù‡Ø§ (Ø¯Ø±Ø§Ø³Ø© Ø£Ø¯Ø¨ÙŠØ©) - Siti Ain Makkiyah (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2017)
TumÄá¸ir bint Amr bin al-Harth bin al-SharÄ«d al-SulamÄ«yah (575-646) or known by the name Khansa 'is the seventh-century Arab poet. Khansa 'was born and raised in the region of Najd. Khansa 'is a very famous poetess during jahili and the Islamic period. Initially he across the Prophet Mohammed, but later converted to Islam. The majority of the poet works contains lament addressed to people who loved one of which is addressed to his two brothers. Researchers study reveals literary analysis, and using descriptive qualitative method. This article uses the literature research by collecting data from multiple reference with regard to lament syi'ir Khansa 'for two brothers namely Shakhr and Mu'awiya.